2016
DOI: 10.4238/gmr.15027848
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel betaine aldehyde dehydrogenase gene from Suaeda corniculata

Abstract: ABSTRACT. Glycine betaine is an important quaternary ammonium compound that is produced in response to several abiotic stresses in many organisms. The synthesis of glycine betaine requires the catalysis of betaine aldehyde dehydrogenase (BADH), which can convert betaine aldehyde into glycine betaine in plants, especially in halotolerant plants. In this study, we isolated the full-length cDNA of BADH from Suaeda corniculata (ScBADH) using reverse transcriptase-polymerase chain reaction and rapid amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…TFs play a vital role in connecting the salt-sensory pathways to the various genes required for plant salt-tolerance (Nishiyama et al 2012). These genes play critical roles in regulating plant stress responses, to various abiotic stress factors including salinity (Joshi et al 2016;Wang et al 2016a). Several studies reported the development of transgenic plants with modified TF expression that improved salt-tolerance (Joshi et al 2016).…”
Section: Engineering Regulatory Elements For Increased Salt Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…TFs play a vital role in connecting the salt-sensory pathways to the various genes required for plant salt-tolerance (Nishiyama et al 2012). These genes play critical roles in regulating plant stress responses, to various abiotic stress factors including salinity (Joshi et al 2016;Wang et al 2016a). Several studies reported the development of transgenic plants with modified TF expression that improved salt-tolerance (Joshi et al 2016).…”
Section: Engineering Regulatory Elements For Increased Salt Tolerancementioning
confidence: 99%
“…Schumacher et al (1999) demonstrated enhanced the salt tolerance in tobacco. Wang et al (2016a) showed that overexpression of a vacuolar-type HC-ATPase C subunit gene from Iris lactea (IrlVHA-c), enhanced the salt tolerance in tobacco. Liu et al (2018) demonstrated that the gene encoding subunit A of the vacuolar H + -ATPase from cotton (GhVHA-A) plays an important role in conferring tolerance to water deficit.…”
Section: Vacuolar Membrane H + -Atpase (V-atpase)mentioning
confidence: 99%
“…In higher plants, BADH catalyzes the key step of GB biosynthesis 23 . In Ammopiptanthus nanus , endogenous expression of AnBADH is strongly induced by exposure to high salt, drought, ABA, heat, or cold 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Glycine betaine (GB), a bipolar quaternary ammonium compound that acts as an osmoprotectant, accumulates in many plant species in response to various abiotic stresses 22 . GB protects plants from abiotic stresses by maintaining the osmotic balance under various abiotic stresses and by stabilizing the quaternary structure of complex proteins 23 . We observed increases in GB content in cassava following exposure to drought, osmotic, or salt stress treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of osmolytes such as glycine betaine (GB), which is synthesized in a pathway in which BADH acts as a critical enzyme, has been recently described in plants growing under abiotic stress, including the water deficit [30], contributing to a higher relative water content, the integrity of cell membranes, stabilization of proteins and detoxification [31]. The relationship of overexpression for BADH biosynthesis with the increase in GB levels and greater tolerance to water deficit has already been observed in plants such as Arabidopsis thaliana [31], Sesuvium portulacastrum [32], and Zea mays [33].…”
Section: Proteins Involved In the Response To Water Deficitmentioning
confidence: 99%